Structural white matter changes in adolescents and young adults with maple syrup urine disease. Issue 6 (25th January 2013) - Klee, D.; Thimm, E.; Wittsack, H. J.; Schubert, D.; Primke, R.; Pentang, G.; Schaper, J.; Mödder, U.; Antoch, A.; Wendel, U.; Cohnen, M.
Abstract: Objective: To get insight into the nature of magnetic resonance (MR) white matter abnormalities of patients with classic maple syrup urine disease (MSUD) under diet control. Methods: Ten patients with classic MSUD and one with a severe MSUD variant (mean age 21.5 ± 5.1 years) on diet and 11 age and sex‐matched healthy subjects were enrolled. Apart from standard MR sequences, diffusion weighted images (DWI), diffusion tensor images (DTI), and magnetization transfer images (MT) were obtained and comparatively analyzed for apparent diffusion coefficient (ADC), tensor fractional anisotropy (FA) and MT maps in 11 regions of interest (ROI) within the white matter. Results: In MSUD patients DWI, DTI and FA showed distinct signal changes in the cerebral hemispheres, the dorsal limb of internal capsule, the brain stem and the central cerebellum. Signal intensity was increased in DWI with a reduced ADC and decreased values for FA. MT did not reveal differences between patients and control subjects. Conclusion: Signal abnormalities in the white matter of adolescents and young adults under diet control may be interpreted as consequence of structural alterations like dysmyelination. The reduced ADC and FA in the white matter with preserved MT indicate a reduction in fiber tracks.